2012
DOI: 10.1111/faf.12004
|View full text |Cite
|
Sign up to set email alerts
|

The global contribution of forage fish to marine fisheries and ecosystems

Abstract: Forage fish play a pivotal role in marine ecosystems and economies worldwide by sustaining many predators and fisheries directly and indirectly. We estimate global forage fish contributions to marine ecosystems through a synthesis of 72 published Ecopath models from around the world. Three distinct contributions of forage fish were examined: (i) the ecological support service of forage fish to predators in marine ecosystems, (ii) the total catch and value of forage fisheries and (iii) the support service of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
327
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 358 publications
(355 citation statements)
references
References 56 publications
5
327
2
5
Order By: Relevance
“…Consequently, reform projections from single-species models may be optimistic for ecosystems in which many piscivorous species are recovered. To partially account for this, we conservatively reduced MSY of all forage fish stocks, which provide a food source for many higher-trophic-level fish and mammals, by 25% (29).…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, reform projections from single-species models may be optimistic for ecosystems in which many piscivorous species are recovered. To partially account for this, we conservatively reduced MSY of all forage fish stocks, which provide a food source for many higher-trophic-level fish and mammals, by 25% (29).…”
Section: Methodsmentioning
confidence: 99%
“…B t+1 = B t + SP t − F t B t , if B t > 0:5 B t + SP t , otherwise , [2] where B t is stock biomass, SP t is the surplus production, and F t is the fishing mortality rate in year t. SP t was calculated from the time series of biomass and catches. We projected population biomass forward 10 y starting with the first year that B < 0.5.…”
Section: Methodsmentioning
confidence: 99%
“…Although not explicitly shown by Essington et al (4), it is reasonable to expect substantial benefits of this harvest strategy to the broader ecosystem, given the critical linkages between forage fish and other species (2,3,8). Long-term empirical studies have demonstrated that seabird breeding success (and ultimately population size) declines precipitously as the abundance of their forage fish prey decreases and foraging time increases (9,10).…”
Section: Fishing's Fingerprintmentioning
confidence: 98%
“…Forage species play an essential and valuable supporting role within marine ecosystems by serving as prey for larger species (2,3). These findings underscore the importance of (i) furthering understanding of the determinants of forage fish collapses, and (ii) of devising exploitation strategies that will maintain their crucial ecological and economic roles.…”
mentioning
confidence: 99%